Revisiting edible insects as sources of therapeutics and drug delivery systems for cancer therapy - Sinha, Barnali; Choudhury, Yashmin (Frontiers in Pharmacology, 2024)
Cancer has been medicine's most formidable foe for long, and the rising incidence of the disease globally has made effective cancer therapy a significant challenge. Drug discovery is targeted at identifying efficacious compounds with minimal side effects and developments in nanotechnology and immunotherapy have shown promise in the fight against this complicated illness. Since ancient times, insects and insect-derived products have played a significant role in traditional medicine across several communities worldwide. The aim of this study was to inspect the traditional use of edible insects in various cultures and to explore their modern use in cancer therapy. Edible insects are sources of nutrients and a variety of beneficial substances with anticancer and immunomodulatory potential. Recently, insect derived bioactive-components have also been used as nanoparticles either in combination with chemotherapeutics or as a nano-cargo for the enhanced delivery of chemotherapeutic drugs due to their high biocompatibility, low bio-toxicity, and their antioxidant and anticancer effects. The crude extracts of different edible insects and their active components such as sericin, cecropin, solenopsin, melittin, antimicrobial peptides and fibroin produce anti-cancer and immunomodulatory effects by various mechanisms which have been discussed in this review.